English Classroom Culture Reformation: How Can It be Done? - Lies Amin Lestari (TEFLIN, 1999)
People say that the teaching of English in Indonesia is unsuccessful. Senor High School graduates, after having been studying English for six years, are unable to use the language in daily communication. One of the causes of the failure, in my opinion, is our classroom Ã¢â¬Ëculture that is not conducive to the learning process. In the classroom students are supposed to sit nicely, listen to the teacher attentively and are obedient to him. The teacher is the only one who is supposed to know everything and therefore becomes the one who dominates the classroom. If this culture, especially during the English class, is not reformed, I think, whatever efforts under